Outcomes in Patients with Moyamoya Syndrome and Sickle Cell Disease: A Systematic Review (2020)
Background: Moyamoya syndrome, a progressive, idiopathic stenosis of the internal carotid arteries, results in increased risk for both ischemic and hemorrhagic strokes. Revascularization procedures have been shown in small studies to be both safe and efficacious for these patients; however, randomized controlled trials are lacking. The goal of this systematic review is to organize the literature evaluating surgical intervention versus conservative medical management. Methods: A systematic review was performed including studies with 3 or more participants with moyamoya syndrome in the setting of sickle cell disease and a measured outcome after either medical or surgical intervention. Relevant studies were identified using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses criteria and a set of predetermined key words. Results: Sixty-one articles were identified with 6 articles ultimately included in this review (N = 122). Of the patients, 73 (59.8%) were revascularized surgically (all indirect procedures), whereas 49 (40.2%) remained on chronic transfusion therapy. Of the patients that underwent indirect revascularization surgery, a total of 1 perioperative (1.4%) and 4 postoperative strokes (5.5%) were reported over 44 months (1 stroke per 53.3 patient-years). In comparison, an average of 46.5% of patients who were receiving chronic transfusions had major events (stroke or transient ischemic attack) while undergoing therapy (1 stroke per 13.65 patient-years, P = 0.00215). Conclusions: We present a large systematic review of the literature regarding outcomes of surgical and medical management for patients with moyamoya syndrome and sickle cell disease. The findings redemonstrate the efficacy and safety of surgical revascularization, and advocate for earlier discussion around surgical intervention. © 2019 Elsevier Inc.